2005
DOI: 10.1002/ad.28
|View full text |Cite
|
Sign up to set email alerts
|

Blurring the Lines, Case Study: Digital Housings, An Exploration of Current CAD/CAM Techniques

Abstract: The work of the New-York based firm Massie Architecture, although as yet small in scale, lies at the cutting edge of digital architectural practice in many senses, not the least of which is the firm's extensive and direct experimentation with fabrication and assembly methods that leverage the computer's capabilities to generate and manage complex data, and to carry these data through from the design phase to the construction of a project. Examples drawn from a number of the practice's recent and current projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The advances in digital design lead researchers to ask if this is a transitional phase from conventional hand techniques to techniques that are completely digital (Mueller, 2006). Research has revealed the complementing advantages through a mix‐mode collaboration of the two media or the so‐called hybrid design approach (Chaszar, 2006; Dorta, 2005; Mueller, 2006), which involves the integrated use of manual and digital tools in the design process. The theory is that the mixed use of tangible and virtual tools can be a catalyst for creativity and the hybrid design environment has great potential to enhance understanding (Casaus, Fargas, & Papuzian, 1993; Dorta, Pérez, & Lesage, 2008).…”
Section: The Hybrid Approach In Contemporary Interior Design Professionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advances in digital design lead researchers to ask if this is a transitional phase from conventional hand techniques to techniques that are completely digital (Mueller, 2006). Research has revealed the complementing advantages through a mix‐mode collaboration of the two media or the so‐called hybrid design approach (Chaszar, 2006; Dorta, 2005; Mueller, 2006), which involves the integrated use of manual and digital tools in the design process. The theory is that the mixed use of tangible and virtual tools can be a catalyst for creativity and the hybrid design environment has great potential to enhance understanding (Casaus, Fargas, & Papuzian, 1993; Dorta, Pérez, & Lesage, 2008).…”
Section: The Hybrid Approach In Contemporary Interior Design Professionmentioning
confidence: 99%
“…Such an approach involves computers in three main aspects: it enables (i) the exploration of complex forms and environmental context, (ii) the optimization of the building components and systems, and (iii) the calculation for comprehensive fabrication and the management for manufacturing and construction process (Kolarevic & Malkawi, 2005). This pioneering application of hybrid design process has emerged at Gehry Partners (Takemori, 2006), WRT Design, and Thread Collective (Chaszar, 2006), and also at many other design firms worldwide.…”
Section: The Hybrid Approach In Contemporary Interior Design Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, we observe a slight shift of focus from object to information which not only challenges the traditional role of the architect but also his relationship with the other disciplines. According to Chaszar (2003), such techniques and approaches to form generation have given rise to a different cognitive model of form as well as a different vocabulary of forms. Third, as observed by Benne (2004), technology is not only added to the existing design processes, but it facilitates 'a combined techno-organizational change', where the respective roles and links among the participants change along with the technology and the knowledge content.…”
Section: Introductionmentioning
confidence: 99%
“…Because the physical model has been traditionally made manually (it often takes several hours to interpret, visualize, hand-cut and build the information conveyed by plans and technical drawings), and because of the advent of digital technology and the subsequent connotations of speed, there has been a tendency to equate model-making with slowness, tediousness and inflexibility.The traditional process is time-consuming, indeed, and is generally lacking in precision.This has contributed to the relegation of (physical) model-making to a second position in the debates dealing with architectural representation in the digital age, despite the fact that several international architectural firms, such as the often-quoted Frank Gehry's studio in California, have successfully pushed model making to the forefront of their design strategies and methods. But since the last ten years or so, some researchers in the architectural computing area started to point to the emergence of new cutting-edge technologies that could be of great relevance to the making of both models and buildings.The publications by Rawson [1], Novitski [2], Eliassen [3], Chaszar [4] and Kenzari [5-6-7] are worth mentioning in this respect.…”
Section: Introductionmentioning
confidence: 99%